Integrated vision functions for the guidance of smart vehicle - Wong, Swee Meng. (2008)
This thesis describes an ICV equipped with a robust electronic driver that consists of several intelligent systems. Three basic vision functions for road navigation - lane finding, obstacle detection and depth assessment of obstacles- are implemented in the real-time vision system.